Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1108/09590550410515515
|View full text |Cite
|
Sign up to set email alerts
|

Situational, consumer, and retailer factors affecting Internet, catalog, and store shopping

Abstract: Most research related to consumer choice of retailers emphasizes retailer attributes and/or consumer characteristics. Since many retail formats, including online retailing, have emerged in recent years, knowledge of how consumers select retail formats must be updated. A source of influence that has been examined to a very limited extent for store retailers but not for emerging retail formats is situational influence. From a modern interactionism perspective, this study investigates the influence of situational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 35 publications
6
99
2
1
Order By: Relevance
“…The findings clearly show the relevance of shopper logistics for the convenience of storebased shopping in the grocery sector confirming previous suppositions of Ingene (1984), Gert andYan (2004) and Granzin et al (2005). In particular, the store-related shopper logistics attributes linked to transportation, picking and packing activities of consumers can be considered as relevant for store-based shoppers.…”
Section: -------------------------Table 3 Near Here -----------------supporting
confidence: 75%
See 1 more Smart Citation
“…The findings clearly show the relevance of shopper logistics for the convenience of storebased shopping in the grocery sector confirming previous suppositions of Ingene (1984), Gert andYan (2004) and Granzin et al (2005). In particular, the store-related shopper logistics attributes linked to transportation, picking and packing activities of consumers can be considered as relevant for store-based shoppers.…”
Section: -------------------------Table 3 Near Here -----------------supporting
confidence: 75%
“…Eastlick and Feinberg, 1999;Ring and Tigert, 2001;Ward, 2001;Gehrt and Yan, 2004;Hansen, 2008). This body of literature considers store-based shopping and related logistics tasks as an 'antithesis' of non-store retailing but does not provide in-depth discussions or empirical insights into the relevance of shopper logistics.…”
Section: Non-store Retailingmentioning
confidence: 99%
“…Previous studies provide evidence on the effect of use context on consumer decision-making [23][24][25][26]. The studies suggest that use situations have a significant impact on consumer choice of products [27], stores [28], and other purchase channels [26].…”
Section: Mobility and Mobile Use Contextmentioning
confidence: 99%
“…The studies suggest that use situations have a significant impact on consumer choice of products [27], stores [28], and other purchase channels [26]. Dabholkar and Bagozzi [24] found that two contextual factors, perceived waiting time and crowding, had significant mediating effects to the attitude towards and use intention of consumer self-service technologies.…”
Section: Mobility and Mobile Use Contextmentioning
confidence: 99%
“…The elements that have been accepted by a substantial number of scholars were further researched in this paper. Baker et al (2002), Grewal (2003, Finn and Louviere (1996) and Gehrt and Yan (2004) outlined the elements of store patronage, as shown in Table 4. Although none of them revealed the entirety of store patronage, each one contributed specific elements, building on the works that preceded their own.…”
Section: Store Patronagementioning
confidence: 99%